SOCIO-ECONOMIC FACTORS AND TEENAGE PREGNANCIES IN AKERIAU SUB-COUNTY, AMURIA DISTRICT - ALWA ESTHER (My University, 2025)
ABSTRACT The study concentrated on the topic socio-economic factors and teenage pregnancies in Akeriau sub-county, Amuria district study used a descriptive mixed research design and it considered a sample size of 86 respondents. Findings of the study revealed that: Economic poverty has a very big influence on teenage pregnancies, that economic poverty creates lack of resources and support resulting in to teenage pregnancies, that there is a relationship between peer pressure and teenage pregnancies, that there is a relationship between peer pressure and teenage pregnancies, that curiosity due to peer pressure contributes on increasing teenage pregnancies and lastly that boys face peer pressure validation of man hood regarding sexual activity leading to teenage pregnancies. The study recommends that: Government should put in place programs to help reduce on increasing levels of poverty within the community, that there is need to sensitize the community on cultural perceptions in order to reduce on increasing teenage pregnancies and lastly that Government and stakeholders should ensure that strict policies are put in place to reduce on teenage pregnancies.